Pengaruh Terapi Murottal Al-Qur’an Terhadap Tingkat Kecemasan Pada Ibu Bersalin Kala I Di PMB ‘Y’ Di Kecamatan Cibinong, Kabupaten Bogor - Emilia, Emilia (STIKes Medistra Indonesia, 2023)
Anxiety can be experienced by anyone under any circumstance, especially in women who give birth face. excessive anxiety in pregnant women can also slow cervical dilatation so that more and prolong labor. Based on this, the anxiety must be addressed in order to avoid complications during delivery. One of the efforts in reducing maternal anxiety is to use murattal therapy, namely sound recordings made by a Qori '(readers of the Qur'an) chant the Qur'an physically contain elements of the human voice, the human voice is an instrument healer which amazing and tools that are easiest to reach.This study was to determine the effect of murottal Al-Qur’an therapy on maternal maternity anxiety on delivery duration of labor at PMB ‘Y’, Kecamatan Cibinong, Kabupaten Bogor period August until December 2022. Research using pre-eksperimental with The study design One Group Pre-Test Post-Test Design. The sample in this study 30 people with purposive sampling. Based on the results of study, maternal anxiety levels before therapy murottal many as 20 respondents (66.7%) were at moderate levels of anxiety and 10 respondents (33.3%) are at a severe anxiety. Smaller than murottal after therapy is given by 15 respondents (50%) are at the level of mild anxiety and 15 respondents (50%) arriving at moderate levels of anxiety. Statistical analysis using the Wilcoxon test p-value 0,000 results (<0.05). There is an effect of murottal Al-Qur’an therapy on maternal maternity anxiety on delivery duration of labor at PMB ‘Y’, Kecamatan Cibinong, Kabupaten Bogor period August until December 2022. Keywords: Labor, Anxiety, Murattal Al-Qur’an Therapy